2007
DOI: 10.1182/blood-2007-06-094508
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-α or homoharringtonine as salvage treatment for chronic myeloid leukemia patients who acquire the T315I BCR-ABL mutation

Abstract: are at odds with the claims on the company's website (http:// www.upstate.com) that this antibody was raised against amino acids 27-37 of human ␤-catenin. As published previously, the 8E7 epitope mapped directly C-terminal to amino acid 35. 3 It is unfortunate that these antibodies with such similar names, commercialized by the same company, have strikingly different specificities. Our observations imply that the 8E4 antibody does not possess the advertised specificity for the dephosphorylated regulatory reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…In the T315I + group, five patients had received interferon-α after the identification of the T315I mutation, and 36 before (30 alone prior to IM, 6 in combination with IM, data not shown). We hypothesize that the fact that some patients received interferon-α after the identification of the T315I mutation, a possible therapeutic option 25 along with omacetaxine mepesuccinate 25,26 in patients not eligible for allogeneic stem cell transplantation, might explain this positive effect. However, it remains unclear whether interferon-α exerts a specific activity on the T315I mutated clone 25 or whether it is simply the withdrawal of the selective agent, the TKI, that improves the outcome of these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the T315I + group, five patients had received interferon-α after the identification of the T315I mutation, and 36 before (30 alone prior to IM, 6 in combination with IM, data not shown). We hypothesize that the fact that some patients received interferon-α after the identification of the T315I mutation, a possible therapeutic option 25 along with omacetaxine mepesuccinate 25,26 in patients not eligible for allogeneic stem cell transplantation, might explain this positive effect. However, it remains unclear whether interferon-α exerts a specific activity on the T315I mutated clone 25 or whether it is simply the withdrawal of the selective agent, the TKI, that improves the outcome of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the fact that some patients received interferon-α after the identification of the T315I mutation, a possible therapeutic option 25 along with omacetaxine mepesuccinate 25,26 in patients not eligible for allogeneic stem cell transplantation, might explain this positive effect. However, it remains unclear whether interferon-α exerts a specific activity on the T315I mutated clone 25 or whether it is simply the withdrawal of the selective agent, the TKI, that improves the outcome of these patients. 18 In this matched pair analysis, the presence of the T315I mutation in CP undoubtedly impaired overall and failurefree survival ( Figures 1A,B,C and 2A,B,C).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even in these advanced cases, Bcr-Abl remains the critical therapeutic target. At this point, reports of successful salvage therapy for CML patients who acquire the T315I mutation are limited to small clinical trials and case reports (41,42). Because SGX393 is active against native Bcr-Abl and the Bcr-Abl T315I mutant, monotherapy with an inhibitor of this type might be sufficient to induce responses in patients harboring only BcrAbl T3151 .…”
Section: Discussionmentioning
confidence: 99%
“…Minami Y, et al reported that monitoring gene mutations in fractionated hematopoietic stem cells and progenitors at diagnosis may help detect the T315I mutation earlier [38]. Standard methods to detect the T315I mutation and the standard management of patients with this mutation in practice need to be established [28,39,40].…”
Section: Discussionmentioning
confidence: 99%